Pengaruh Model Pembelajaran Project Based Learning terhadap Kemampuan Menulis Teks Narasi - Dina Fitri Setyawati; Afakhrul Masub Bakhtiar; Iqnatia Alfiansyah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The purpose of this study was to determine the effect of uring the Project Based Learning model on the ability to write narrative texts in grade IV students at UPT SDN 18 Gresik. The type of research used is quantitative research with an experimental reseacrh method. The experimental research method used is a quasi esperiment, because in this study the researcher cannot control all variables. The subjects involved in this research were class 4 of UPT SDN 18 Gresik in the 2024/2025 academic year, totaling 54 students who were divided into 2 classes, namely class IVA and IVB. The analysis used is descriptive statistical analysis and inferential statistical analysis. Based on the result of the analysis that has been done, the average value of the post-test value of the experimental class is 83,77. While in the control class, the average value is 78,56. From these results, it it proven by hypothesis testing using the independent sample T Test at a significance level of α = 0,05 showing a Sig value of 0,000, which means the Sig value < 0,05.